(untitled) (Vietnam Journal of Community Medicine, 2026)
Mesenchymal stem cells (MSCs) are defined as residual stem cells in most adult organs, specifically adipose tissue (ASC or ADSC). ADSCs have been identified in the underlying tissue, which plays an important role in repairing and regenerating the skin through a variety of proven mechanisms. These involve different skin and address disadvantages or limitations in conventional treatments.